Three-Dimensional Iron Oxide Nanoparticle-Based Contrast-Enhanced Magnetic Resonance Imaging for Characterization of Cerebral Arteriogenesis in the Mouse Neocortex - de Bortoli, Till; Boehm-Sturm, Philipp; Koch, Stefan P.; Nieminen-Kelhä, Melina; Wessels, Lars; Mueller, Susanne; Ielacqua, Giovanna D.; Klohs, Jan; Vajkoczy, Peter; Hecht, Nils (Frontiers in Neuroscience, 2021)
Purpose: Subsurface blood vessels in the cerebral cortex have been identified as a bottleneck in cerebral perfusion with the potential for collateral remodeling. However, valid techniques for non-invasive, longitudinal characterization of neocortical microvessels are still lacking. In this study, we validated contrast-enhanced magnetic resonance imaging (CE-MRI) for in vivo characterization of vascular changes in a model of spontaneous collateral outgrowth following chronic cerebral hypoperfusion. Methods: C57BL/6J mice were randomly assigned to unilateral internal carotid artery occlusion or sham surgery and after 21 days, CE-MRI based on T2*-weighted imaging was performed using ultra-small superparamagnetic iron oxide nanoparticles to obtain subtraction angiographies and steady-state cerebral blood volume (ss-CBV) maps. First pass dynamic susceptibility contrast MRI (DSC-MRI) was performed for internal validation of ss-CBV. Further validation at the histological level was provided by ex-vivo serial two-photon tomography (STP). Results: Qualitatively, an increase in vessel density was observed on CE-MRI subtraction angiographies following occlusion, however, a quantitative vessel tracing analysis was prone to errors in our model. Measurements of ss-CBV reliably identified an increase in cortical vasculature, validated by DSC-MRI and STP. Conclusion: Iron oxide nanoparticle-based ss-CBV serves as a robust, non-invasive imaging surrogate marker for neocortical vessels, with the potential to reduce and refine preclinical models targeting the development and outgrowth of cerebral collateralization.